2017
DOI: 10.1111/tbed.12698
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge gaps and research priorities inStaphylococcus aureusmastitis control

Abstract: SummaryThis study assessed knowledge gaps and suggested research priorities in the field of Staphylococcus aureus mastitis. Staphylococcus aureus infecting the mammary gland remains a major problem to the dairy industry worldwide because of its pathogenicity, contagiousness, persistence in the cow environment, colonization of skin or mucosal epithelia, and the poor curing efficacy of treatments. Staphylococcus aureus also constitutes a threat to public health due to food safety and antibiotic usage issues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
202
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(231 citation statements)
references
References 168 publications
3
202
0
9
Order By: Relevance
“…When the induced immune response is not effective in clearing the pathogen, the duration of the mastitis will increase and influx of leukocytes will continue, resulting in more tissue damage, and potentially a more severe mastitis. Although the level of bMEC activation by S. aureus likely contributes to the severity of an IMI, it is important to emphasize that the clinical severity of IMI depends on several factors, such host conditions and production of bacterial virulence factors [44]. Recently, we observed that S. aureus belonging to CC479 are associated with clinical rather than subclinical mastitis cases in cattle [23].…”
Section: Discussionmentioning
confidence: 96%
“…When the induced immune response is not effective in clearing the pathogen, the duration of the mastitis will increase and influx of leukocytes will continue, resulting in more tissue damage, and potentially a more severe mastitis. Although the level of bMEC activation by S. aureus likely contributes to the severity of an IMI, it is important to emphasize that the clinical severity of IMI depends on several factors, such host conditions and production of bacterial virulence factors [44]. Recently, we observed that S. aureus belonging to CC479 are associated with clinical rather than subclinical mastitis cases in cattle [23].…”
Section: Discussionmentioning
confidence: 96%
“…With regard to Staphylococcus aureus mastitis, Rainard et al. () identify three priorities for further research: (i) understanding the molecular basis for pathogenesis of S. aureus mastitis; (ii) identifying staphylococcal antigens inducing protection; and (iii) determining cell‐mediated immune responses to infection and vaccination. Klaas and Zadoks () cover the topic of environmental mastitis in dairy cattle.…”
Section: Editorialmentioning
confidence: 99%
“…Our review focuses on virulence factors in coagulase positive Staphylococci isolated from animals. S. aureus is not discussed in this paper due to the existence of a number of recent review articles covering this species; see for example (Zecconi and Scali 2013;Scali et al 2015;Mutters et al 2016;Ballhausen et al 2017;Aires-de-Sousa 2017;Rainard et al 2018).…”
Section: Introductionmentioning
confidence: 99%